2020
DOI: 10.1101/2020.02.19.20025031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A descriptive study of the impact of diseases control and prevention on the epidemics dynamics and clinical features of SARS-CoV-2 outbreak in Shanghai, lessons learned for metropolis epidemics prevention

Abstract: Objective: To describe and evaluate the impact of diseases control and prevention on epidemics dynamics and clinical features of SARS-CoV-2 outbreak in Shanghai. Design: A retrospective descriptive study Setting: China Participants: Epidemiology information was collected from publicly accessible database. 265 patients admitted to Shanghai Public Health Center with confirmed COVID-19 were enrolled for clinical features analysis. Main outcome measure: Prevention and control measures taken by Shanghai governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 11 publications
2
44
0
1
Order By: Relevance
“…16 Serum levels of ALT and AST in severe to critical cases were significantly higher than those in mild to moderate cases among 265 patients with COVID-19 from Shanghai. 17 Similarly, patients admitted to the ICU were more likely to have high levels of serum ALT, AST, and total bilirubin. 18,19 In 52 critically ill patients with multiple organ damage, 35 (67%) had ARDS, 15 (29%) had acute kidney injury, 15 (29%) had liver injury, and 12 (23%) had cardiac injury.…”
Section: Laboratory Changes Of Liver Function Test In Patients With Cmentioning
confidence: 99%
“…16 Serum levels of ALT and AST in severe to critical cases were significantly higher than those in mild to moderate cases among 265 patients with COVID-19 from Shanghai. 17 Similarly, patients admitted to the ICU were more likely to have high levels of serum ALT, AST, and total bilirubin. 18,19 In 52 critically ill patients with multiple organ damage, 35 (67%) had ARDS, 15 (29%) had acute kidney injury, 15 (29%) had liver injury, and 12 (23%) had cardiac injury.…”
Section: Laboratory Changes Of Liver Function Test In Patients With Cmentioning
confidence: 99%
“…Huang reported that prothrombin time and D-dimer levels on admission were higher in intensive care unit (ICU) patients than in non-ICU patients [11]. Plasma concentrations of IL-2, IL-7, Zhang et al [46] Liu et al [47] Yang et al [48] Wang et al [45] Lu et al [49] Liu et al [50] Huang et al [11] Liu et al [51] Chen et al [ IL-10, and TNF-α were higher in ICU patients. In Wang's study [45], ICU patients had higher white blood cell and neutrophil counts, as well as higher levels of D-dimer, creatine kinase, and creatine.…”
Section: Laboratory Findings A) Diagnostic Tests-reverse Transcriptiomentioning
confidence: 99%
“…CT findings are not always consistent with RT-PCR, which is not surprising as CT and RT-PCR do not explore the same issues. Some patients with positive RT-PCR had normal CT [2,6], but may later develop pneumonia, while others would not [6]. Some patients with negative RT-PCR results had marked viral pneumonia features on CT; some RT-PCR results would become positive after repeated tests with about a mean Please note that due to the time sensitive nature of the work presented in this article, standard peer-review has been bypassed to ensure rapid publication.…”
Section: What Is the Balance Between Ct And Rt-pcr?mentioning
confidence: 99%